2021
DOI: 10.1038/s41467-021-21217-0
|View full text |Cite
|
Sign up to set email alerts
|

LETR1 is a lymphatic endothelial-specific lncRNA governing cell proliferation and migration through KLF4 and SEMA3C

Abstract: Recent studies have revealed the importance of long noncoding RNAs (lncRNAs) as tissue-specific regulators of gene expression. There is ample evidence that distinct types of vasculature undergo tight transcriptional control to preserve their structure, identity, and functions. We determine a comprehensive map of lineage-specific lncRNAs in human dermal lymphatic and blood vascular endothelial cells (LECs and BECs), combining RNA-Seq and CAGE-Seq. Subsequent antisense oligonucleotide-knockdown transcriptomic pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 127 publications
2
17
0
1
Order By: Relevance
“…This study complements our previous findings, where we analyzed the functionality of human lncRNAs in vascular biology by performing ASO-mediated knockdown of 2 LEC- and 2 BEC-specific lncRNAs followed by CAGE-Seq [ 18 ]. Here, we presented the early control steps in which we carefully characterized the transcriptional impact on LECs and BECs of two commercially available negative control ASOs.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This study complements our previous findings, where we analyzed the functionality of human lncRNAs in vascular biology by performing ASO-mediated knockdown of 2 LEC- and 2 BEC-specific lncRNAs followed by CAGE-Seq [ 18 ]. Here, we presented the early control steps in which we carefully characterized the transcriptional impact on LECs and BECs of two commercially available negative control ASOs.…”
Section: Discussionsupporting
confidence: 73%
“…Next, we investigated whether the effects of ASO transfection on the general transcriptome of LECs or BECs were consistent between the two negative control ASOs by comparing them to the untransfected reference CAGE-Seq samples (Additional file 2 , refer to the original study [ 18 ] for further details). For the comparison, we considered only genes displaying a | log2FC| > 1 and an FDR corrected P -value < 0.05.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating research has revealed that many lncRNAs play vital roles in cancer tumorigenicity ( Yari et al, 2019 ; Feng et al, 2020 ) and progression ( Zhu et al, 2017 ; Gong et al, 2020 ), are aberrantly expressed in a variety of cancers, and participate in many biological functions, such as cell proliferation ( Ducoli et al, 2021 ; Shen et al, 2021 ), epithelial-to-mesenchymal transition (EMT) ( Grelet et al, 2017 ; Zhao et al, 2017 ), invasion ( Schmidt et al, 2016 ; Jin et al, 2019 ), migration ( Liu L. et al, 2019 ; Zhao et al, 2018 ), angiogenesis ( Zhao et al, 2020 ; Li et al, 2021 ), and differentiation ( Luo et al, 2019 ; Tong et al, 2020 ). Moreover, lncRNAs can also function as competing endogenous RNAs (ceRNAs) ( Wang et al, 2017 ; Zhou et al, 2019 ), transcription factors ( Long et al, 2017 ; Ducoli et al, 2021 ), and in post-transcriptional processing ( Zhang et al, 2018 ; Botti et al, 2019 ). All these findings suggest that lncRNAs may be able to serve as potential cancer biomarkers, ameliorating some of the current problems caused by cancer.…”
Section: Introductionmentioning
confidence: 99%